Fgf-23 and vascular calcification in a peritoneal dialysis population with residual renal function - Santos, S. (2015)
Introduction and Aims: Fibroblast growth factor 23 (FGF-23) induces phosphaturia. Its clinical impact is beyond mineral bone disease in chronic kidney disease (CKD), being coupled with vascular calcification and mortality. Residual renal function (RRF) is associated with significant capacity to excrete phosphate in peri- toneal dialysis (PD). Besides testing whether FGF-23 is still related with glomerular filtration rate (GFR) and phosphate excretion in this late stage of CKD (5d), we aimed to explore its link with vascular calcification.Subjects and Methods: FGF-23 (C terminal) was measured in forty prevalent PD patients with RRF, aged 61.5 (51.0-67.0) years old, in renal replacement therapy (RRT) for 43.5 (23-80.0) months; 36.6% were female, 19.5% had diabetes mellitus and 37.5% were under automated PD regimen; 80% were on PD first, and only 20% had previous RRT. Relevant variables including dietary phosphate (P) intake, CKD-bone laboratory parameters, serum 25-hydroxyvitamin D, magnesium (Mg) levels, GFR, urinary phosphate, fractional excretion of phosphorus (FEP), albumin, proBNP and Adragão vascular calcification score were explored. Results: Median levels (25-75% range) of serum variables were: FGF-23 1997 (1623-2149) RU/mL, Mg 0.94 (0.8-1.0) mmol/L, 25-hydroxyvitamin D 30 (18-47) nmol/L, calcium 2.2 (2.0-2.37) mmol/L, phosphorus 1.69 (1.30-1.90) mmol/L, PTH 429 (309-626) pg/mL. FGF-23 correlated positively with serum phosphate (r = 0.39, p = 0.013) and negatively with urine volume (r = -0.48, p = 0.001), phosphaturia (r = -0.594, p < 0.0001) and GFR (r =-0.61,p < 0.0001). However, FGF-23 was not significantly correlated with age, total time of RRT, dietary P, FEP, Mg, nor 25-hydroxyvitamin D. High FGF-23 group had higher FEP. GFR was the single inde- pendent predictor of increased FGF-23. On the other hand, neither FGF-23 nor low FEP/FGF-23 ratio were significantly associated with the vascular calcification score. Only albumin (lower), magnesium (lower) and proBNP (higher) levels significantly differed in calcified versus non-calcified patients (all with p < 0.05). Conclusions: In our population, FGF-23 was not associated with vascular calcification. GFR was the single independent predictor of increased FGF-23 in patients with diuresis. Increment of FGF-23 in PD patients signalizes an active endocrine phosphaturic process compensating renal function loss, as expressed by higher fractional excretion of phosphorus. It alerts for dietetic and therapy optimization. However, its link with vascular calcification still lacks validation.